Lobbying and the responsible firm: Agenda‐setting for a freshly conceptualized field. (5th February 2018) - Anastasiadis, Stephanos; Moon, Jeremy; Humphreys, Michael
Abstract : "Responsible lobbying" is an increasingly salient topic within business and management. We make a contribution to the literature on "responsible lobbying" in three ways. First, we provide novel definitions and, thereby, make a clear distinction between lobbying and corporate political activity. We then define responsible lobbying with respect to its content, process, organization, and environment, resulting in a typology of responsible lobbying, a conceptual model that informs the rest of the paper. Second, the paper provides a thematic overview of the current literature underpinning lobbying and the responsible firm, and the underlying paradigms informing this literature. Third, the paper makes specific suggestions for a future research agenda, ending with a consideration of methodological implications of such research.